Peculiarities of structural properties of masonry from hollow block units and their estimation/Mūro iš tuštymėtų blokelių konstrukcinių savybių ypatumai ir jų įvertinimas - Bronius Jonaitis; Gediminas Maršiukaitis; Vytautas Papinigis; Juozas Valivonis (Journal of Civil Engineering and Management, 2001)
Performed analyses of investigations have shown that properties of masonry from hollow blocks depend on many factors, and on material type and shape of the blocks including. But there is no unified method for determining the main structural properties-the compressive strength and modulus of elasticity. Theoretical investigations into masonry from hollow blocks and analysis of character of failure have shown that horizontal stress due to vertical loads has great influence on the strength of such masonry. The failure is initiated by vertical cracks crossing transverse webs. Values of strengths of concentrically compressed masonry calculated according to codes [2, 3] lead to different deviations from experimental results. Lower deviations for masonry of blocks are obtained according to [2] than according to [3]. Strength of masonry of calcium silicate blocks calculated by [3] is greater than that determined by experiments. Modulus of elasticity of such type masonry is lower than that of the same strength masonry from concrete blocks. Different calculation methods give different values of deformation modulus. The best agreement with experimental values of modulus of elasticity is given by the calculation method [2]. For selection types of hollow blocks for masonry and determination of design characteristics it is recommended to take average values determined by operating codes [2, 3] and to evaluate influence of shape and size of hollows on transverse tensile strength of blocks.